The Implementation of Learning Device using Problem-Based Learning Model to Optimize Students’ Science Problem-Solving Skill - Yusuf, Muhammad; Rahman, Sari Rahayu (International Journal of Active Learning, 2019)
A research on learning device development using problem-based learning model on junior high students has been conducted. The research aims to describe the implementation result of learning device using a problem-based learning model to optimize high school students? science problem-solving skill. This research is conducted as an effort to improve education quality especially the learning process. It is a Research and Development (R&D) kind of research which is to develop learning device. 4D steps by Thiagarajan are applied in developing learning device. In addition, the learning device is tested for validity and feasibility by the expert. The research process is conducted through some phases, such as device development phase, expert test, limited test, and extended tryout on science subject of Junior High school grade VIII in Bone Bolango district. This research discusses the implementation result on an extended tryout. The findings show that the developed learning device can optimize learning management, students? activities, and students? response in which each is in good and very good category. Meanwhile, individual student learning achievement is 91% accomplished. Problem-based learning model can be applied at high school students of grade VIII especially on science subject, lesson of motion and energy.